Plasma and chemical-induced graft polymerization on the surface of starch-based biomaterials aimed at improving cell adhesion and proliferation - Elvira, C. (2003)
Plasma and chemical induced graft polymerization of acrylic monomers on starch-based biomaterials has been performed with the aim to improve cell adhesion and proliferation on the surface of the polymers, in order to adequate their properties for bone tissue engineering scaffolding applications. Plasma and chemical surface activation was aimed to induce the polymerization of acrylic polar monomers being carried out by applying a radio frequency plasma and expose the samples to a mixture of Ar/O2, or by immersion in a H2O2/(NH4)2S2O8 solution with UV radiation, respectively. Both procedures were followed by the graft polymerization of the corresponding monomers. Polymer grafting was analyzed by Fourier transformed infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) and by contact angle measurements. Properties such as mechanical performance, swelling degree, and degradation behavior, as well as bioactivity, have been studied and compared for the different activation methods. Finally, preliminary cell adhesion and proliferation tests were performed, using goat bone marrow cells, showing a remarkable improvement with respect to original non-surface modified starch-based biomaterials.